Village in the sky - McDevitt, Jack (McDevitt, Jack. Alex Benedict novels., 2023)
When an entire town seemingly vanishes from a planet with conditions favorable to life, Alex Benedict and his archaeological crew must solve the mystery of how these aliens disappeared so rapidly--and why--which raises the stakes as they each look to maketheir mark on history.